Surface Modified MXene‐Based Nanocomposites for Electrochemical Energy Conversion and Storage - Yu, Hong; Wang, Yonghui; Jing, Yao; Ma, Jianmin; Du, Cheng‐Feng; Yan, Qingyu (Small (Weinheim an der Bergstrasse, Germany), 2019)
In recent years, the rapidly growing attention on MXenes makes the material a rising star in the 2D materials family. Although most researchers' interests are still focused on the properties of bare MXenes, little attention has been paid to the surface chemistry of MXenes and MXene‐based nanocomposites. To this end, this Review offers a comprehensive discussion on surface modified MXene‐based nanocomposites for energy conversion and storage (ECS) applications. Based on the structure and reaction mechanism, the related synthesis methods toward MXenes are briefly summarized. After the discussion of existing surface modification techniques, the surface modified MXene‐based nanocomposites and their inherent chemical principles are presented. Finally, the application of these surface modified nanocomposites for supercapacitors (SCs), lithium/sodium–ion batteries (LIBs/SIBs), and electrocatalytic water splitting is discussed. The challenges and prospects of MXene‐based nanocomposites for future ECS applications are also presented. Recently, MXenes have gained increasing attention in the field of energy conversion and storage (ECS). Meanwhile, the unique surface chemistry of MXenes endows them with great potential in the construction of 2D based nanocomposites. To this end, the present work offers a comprehensive summary of surface modified MXene‐based nanocomposites for ECS applications.